ChemInform Abstract: A Unique Alkylation of Azobenzenes with Allyl Acetates by RhIII‐Catalyzed C—H Functionalization. Issue 39 (September 2015) - Deng, Hong; Li, Hongji; Wang, Lei
Abstract The direct o‐alkylation of a broad spectrum of azobenzenes is best carried out in the presence of allyl acetate (II).